Secure and Differentiated Fog-Assisted Data Access for Internet of Things. (15th May 2021) - Yu, Ping; Ni, Wei; Zhang, Hua; Ping Liu, Ren; Wen, Qiaoyan; Li, Wenmin; Gao, Fei
Abstract: The ability of Fog computing to admit and process huge volumes of heterogeneous data is the catalyst for the fast expansion of Internet of things (IoT). The critical challenge is secure and differentiated access to the data, given limited computation capability and trustworthiness in typical IoT devices and Fog servers, respectively. This paper designs and develops a new approach for secure, efficient and differentiated data access. Secret sharing is decoupled to allow the Fog servers to assist the IoT devices with attribute-based encryption of data while preventing the Fog servers from tampering with the data and the access structure. The proposed encryption supports direct revocation and can be decoupled among multiple Fog servers for acceleration. Based on the decisional q -parallel bilinear Diffie–Hellman exponent assumption, we propose a new extended q -parallel bilinear Diffie–Hellman exponent (Eq -PBDHE) assumption and prove that the proposed approach provides 'indistinguishably chosen-plaintext attacks secure' data access for legitimate data subscribers. As numerically and experimentally verified, the proposed approach is able to reduce the encryption time by 20% at the IoT devices and by 50% at the Fog network using parallel computing as compared to the state of the art .